2005
DOI: 10.1007/s10669-005-4292-8
|View full text |Cite
|
Sign up to set email alerts
|

New Device Against Non-Thermal Effects from Mobile Telephones

Abstract: Objectives: The aim of this study is to initiate research in the field of biomedical engineering geared towards a reduction of non-thermal effects on the brain due to the use of mobile telephones. This line of research employs devices attached to the back of cellular-telephone cases.Methods: Under electromagnetic-environment controlled conditions EEG records have been obtained in 16 healthy subjects, with their eyes open at the base-line. These records were compared with the use of the mobile telephone with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Commonly used scalp electrodes consist of Ag-AgCl disks, less than 3 mm in diameter, with long flexible leads that can be plugged into an amplifier. The International Federation of Societies for Electroencephalography and Clinical Neurophysiology has recommended the conventional electrode setting (also called [10][11][12][13][14][15][16][17][18][19][20] for 21 electrodes (excluding the earlobe electrodes).…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Commonly used scalp electrodes consist of Ag-AgCl disks, less than 3 mm in diameter, with long flexible leads that can be plugged into an amplifier. The International Federation of Societies for Electroencephalography and Clinical Neurophysiology has recommended the conventional electrode setting (also called [10][11][12][13][14][15][16][17][18][19][20] for 21 electrodes (excluding the earlobe electrodes).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…In another research by H.D Costa et al [6] in 2003 concluded that full power mode exposure may influence human brain activity than standby mode. In 2005 J L Bardasano [15] and colleagues concluded a study by stating that use of a protective device can reduce the effect of mobile phone radiation. A study on "Influence of a 900MHz signal with gender on EEG by Eleni Nanou [11] and colleagues concluded that "without radiation the spectral power of males is greater than of females, while under exposure the situation is reversed".…”
Section: Introductionmentioning
confidence: 99%
“…We find several programs in the central nervous system which schedule the death of mobiles, which are activated by internal alterations (genetic features of the patient) or external (biological, chemical, such as exposure to toxins, heavy metals in drinking water, pesticides, and others, and physical elements such as artificial and uncontrolled electromagnetic fields. (Bardasano et al 2005) The EEG shows the influence of mobile phones on man. In the field of Biomedical Engineering, research should contemplate at least the following aspects: (a) The General Adaptation Syndrome to changes in the state of mater and energy.…”
Section: Methodological Observationmentioning
confidence: 99%
“…Aruna et al [7] in a study in 2011 using EEG analysis, concluded that GSM mobile phone has larger effect on brain compared to CDMA phones.. In another research by H.D Costa et al [8] in 2003 concluded that full power mode exposure may influence human brain activity than standby mode. In 2005 J L Bardasano [9] and colleagues concluded a study by stating that use of a protective device can reduce the effect of mobile phone radiation.…”
Section: Introductionmentioning
confidence: 99%